Analysis of the Promotional Communication Strategy of the Purworejo Regency Regional Library in Attracting Public Interest - Guriani, Devi; Sagita, Titis (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This study aims to analyze the promotional communication strategies implemented by the Regional Library of Purworejo Regency in attracting public interest in library services and increasing public awareness of the importance of libraries as centers of information and literacy. Methodology: This study employed a descriptive qualitative approach. Data were collected through semi-structured interviews, observations, and documentation. The research informants consisted of the head of the library, library staff, and library visitors selected purposively. Data analysis used an interactive model involving data reduction, data presentation, and conclusion drawing through source and technique triangulation. Main Findings: The findings showed that promotional communication strategies were carried out through mobile library services, smart cars, socialization programs, book fairs, websites, training activities, and other promotional media. These strategies succeeded in increasing public awareness of the importance of libraries. However, the implementation still faced several obstacles, including limited human resources, insufficient budget, suboptimal use of digital media, and broad geographical conditions. Novelty/Originality of this study: The novelty of this study lies in its focus on the promotional communication strategies of regional libraries within the local community context of Purworejo Regency by connecting geographical conditions, social characteristics of the community, promotional barriers, and the effectiveness of communication strategies implemented by the regional library in a more contextual and comprehensive manner.